Compensating farmers for ecosystem services: Lessons and an agenda for innovation - Wollenberg, Eva Karoline; Tennigkeit, Timm; Dinesh, Dhanush; Baumert, Sophia; Röhrig, Felicitas; Kirfel-Rühle, Lisa; Zeppenfeldt, Leanne (2022)
The CompensACTION Initiative aims to promote payments for ecosystem services (PES) to improve smallholder farmers’ incomes at large scales while incentivizing climate action, sustainable farming and other environmental outcomes. Key drivers for scaling up PES programs are increasing farmers’ benefits in PES schemes, using public finance to leverage private sector capital, and facilitating PES project readiness. Priority areas for action to meet the CompensACTION Initiative objectives are to: • Foster technical innovation and disruption to support low-cost, high- volume PES transactions. • Increase public and private investment to scale up PES programs. • Support public policy reform to establish national frameworks for PES schemes. • G7 members and other countries can play a leadership role in mobilizing action.